If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15(z + -3) = 25z Reorder the terms: -15(-3 + z) = 25z (-3 * -15 + z * -15) = 25z (45 + -15z) = 25z Solving 45 + -15z = 25z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-25z' to each side of the equation. 45 + -15z + -25z = 25z + -25z Combine like terms: -15z + -25z = -40z 45 + -40z = 25z + -25z Combine like terms: 25z + -25z = 0 45 + -40z = 0 Add '-45' to each side of the equation. 45 + -45 + -40z = 0 + -45 Combine like terms: 45 + -45 = 0 0 + -40z = 0 + -45 -40z = 0 + -45 Combine like terms: 0 + -45 = -45 -40z = -45 Divide each side by '-40'. z = 1.125 Simplifying z = 1.125
| 60+3d=8d+60 | | 2v=68 | | 20x+55=40x+15 | | 7+2=311 | | (y-30)+y+90=180 | | C=2(pi)8.50 | | 6(j-7)+5(2j+3)=76 | | M^2+4m+4-n^2=0 | | -3x-2y=12 | | 17=-5(r-5)+11 | | a-28=19 | | y^2-4x-2y-3=0 | | w=p(1+rt) | | 1/3(9x+12) | | 4(2x-3)-2(x+1)= | | 30x+25=40x+15 | | 5-(-3)=8 | | 13y+19-=6(9+y)+14 | | 3(t-8)+20=5 | | Y=(-3)+2 | | N/4=n+3/6 | | 14-2x=3x-6 | | (2y^2-10y)/(25y-5y^2) | | 21y+4=7 | | 0.3(5+2x)+1.1x=3.1 | | 5x-5y-3z=26 | | 2(w+4)=5(w+1) | | 11-2x=-23 | | -x+5y+4z=-53 | | x+y-z=-4 | | 2y^2-10y/25y-5y^2 | | 9r-2=3(r-2)-10(2-4r) |